Fatigue in Patients with Chronic Hepatitis B living in North America: Results from the Hepatitis B Research Network (HBRN) - Evon, Donna M. (Dig Dis Sci, 2016)
BACKGROUND: Fatigue is a common symptom of liver disease but not well-characterized in patients with chronic hepatitis B virus (HBV). AIMS: We assessed the rate of fatigue using a validated instrument in patients with HBV and identified demographic, virologic, and clinical features associated with fatigue in a cross-sectional cohort study from the Hepatitis B Research Network (HBRN). METHODS: Participants were English and Spanish-speaking adults with chronic HBV who were not pregnant nor on treatment. Fatigue was measured using the PROMIS(®) Fatigue 7-item Short Form. RESULTS: The sample included 948 adults: median age 42; 51% female; 71% Asian; 74% college educated; 77% employed; 41% inactive HBV carriers; 36% with active chronic disease; and 2% with advanced fibrosis, defined as AST-Platelet Ratio Index (APRI) > 1.50. Patients with chronic HBV had a mean fatigue T-score of 46.8 ±SD=7.9, compared to a mean fatigue T-score of 50.0 ± 10 in the U.S. general population (p<.0001). In univariate analyses, greater fatigue was associated with demographic and clinical features such as female sex, lower income, more comorbidities, higher APRI score, and poorer mental health (p<0.05). In multivariate analysis, female sex (p<.001), poorer mental health (p <.001), APRI score (p=.005) and history of diabetes (p=.039) were the strongest independent predictors. CONCLUSIONS: The frequency of fatigue in this large cohort of North American chronic HBV patients may be equal to or lower than that reported in the U.S. general population. Patients with advanced fibrosis, more comorbidities, and poorer mental health report worse fatigue.